PENGARUH INKLUSI KEUANGAN DAN PERAN LEMBAGA KEUANGAN MIKRO TERHADAP KINERJA UMKM DI KECAMATAN SEBERANG ULU I KOTA PALEMBANG - Kosim, Belliwati; Safitri, Ervita; Sindi, Sindi (Universitas Muhammadiyah Palembang, 2021)
This study aimed to determine the effect of financial inclusion and the role of microfinance institutions on the performance of MSMEs in Seberang Ulu I District, Palembang city. This study used quantitative methods, namely by presenting research results in the form of number sorstatistics to test hypotheses. The population of this research was MSME actorsin Seberang Ulu I District, Palembang cityas many as 436 units. The sample in this study was 173 units. This study used quantitative analysis methods. The data used in this study was primary data obtained from filling out questionnaires conducted by respondents. Then the data was processed using multiple liner analysis techniques, based on the results of the analysis showed that the variables of Financial Inclusion and the Role of Microfinance Institutions had an effect on the performance of MSMEs. It was proven by the results of the analysis of the coefficient of determination where the variable of Financial Inclusion and Microfinance Institutionson MSME Performance was 56% and the remaining 44% was in fluenced by other variables not mentioned in this study.